Penerapan Metode Word Square dalam Meningkatkan Hasil Belajar IPS Materi Penggunaan Uang Peserta Didik Kelas III A SD Negeri Kasreman di Semester II Tahun Pelajaran 2018/2019 - Juprihadi Juprihadi (Universitas Sebelas Maret, 2019)
This research is a Class Action Research (CAR) with the purpose to analyze the application of WordSquare Method in increasing the learning outcome of social science about the money utility on the students of Class III A the Elementary School of Kasreman on the Second Semester of the 2018/2019 year academic. The subjects of this research are the students of Class III A the Elementary School of Kasreman on the Second Semester of the 2018/2019 year academic as much as twenty four children; consist of fifteen boys and nine girls. The data resources of this research are relating with learning activities and learning outcomes. Techniques of collecting data of this research are non test technique and test technique. The instruments of collecting data of this research are the sheets of observation and the camera application on the hand phone and also daily test. Technique of analyzing data of this research is comparative description. The procedure of this research is the Kemmis and Mc Taggart’s spiral model that consist of two cycles; First Cycle and Second Cycle. Each cycle is consisting of two meetings. The results of this research are 1) the application of WordSquare Method in increasing the learning outcome of social science about the money utility is a group task by searching, finding and signing the concepts inside the WordSquare during the timeline,2) the application of WordSquare Method in increasing the learning outcome of social science about the money utility is is in a small group, consist of four members, 3) the application of WordSquare Method in increasing the learning outcome of social science about the money utility are increasing the learning activities; actively in discussing, actively in answering the questions from the teacher and other students and actively in asking to the teacher, 4) the application of WordSquare Method in increasing the learning outcome of social science about the money utility has a good group task learning outcomes, 5) the application of WordSquare Method in increasing the learning outcome of social science about the money utility has a good learning outcomes. The learning outcomes on the Early Condition are 60,83 for the average and 58,33% for the completeness. The learning outcomes on the First Cycle are 71,25 for the average and 66,66% for the completeness. The learning outcomes on the Second Cycle are 83,95 for the average and 83,33% for the completeness.